Pengaruh Pengetahuan Investasi, Kemampuan Finansial, Lingkungan Keluarga Terhadap Minat Investasi Mahasiswa Fakultas Ekonomi Universitas Muhammadiyah Ponorogo - Yeni Nur Asrifah Yeni; Titi Rapini Titi Rapini; Riawan Riawan (LPPM Universitas BSI, 2022)
This study aims to determine the effect of Investment Knowledge, Financial Ability and Family Environment on Investment Interest of Students of the Faculty of Economics, University of Muhammadiyah Ponorogo. The population of this study were all active students of the Faculty of Economics, University of Muhammadiyah Ponorogo batch 2018, 2019, 2020, and 2021 with a sample of 88 students. In this study, the sampling method used is probability sampling, namely disproportionate stratified random sampling. The data collection technique was carried out by distributing online questionnaires to students of the Faculty of Economics. The analytical method used in this study was multiple linear regression analysis. The results of this study indicate that 1) investment knowledge has an effect on investment interest in students of the Faculty of Economics, Muhammadiyah University of Ponorogo with a significance of 0.000. 2) Financial Ability has no effect on the Investment Interest of Students of the Faculty of Economics, University of Muhammadiyah Ponorogo with a significance of 0.182. 3) Family environment affects the investment interest of students of the Faculty of Economics, University of Muhammadiyah Ponorogo with a significance of 0.024. 4) the independent variables simultaneously affect investment interest by 47.6% while the remaining 52.4% is influenced by other variables.